Social response to crime in the digital era – the importance of digital criminology and criminal legislation - Ilić, Aleksandra; Bodrožić, Ivana; Milošević, Mladen (Sociološki pregled, 2025)
Modern life based on digitalization significantly influences the characteristics of crime, which is the focus of digital criminology as a specific approach to studying criminal phenomena in the digital era. Given the complexity of the phenomenon, the paper emphasizes the importance of considering the aforementioned issue in all dimensions. The victim’s perspective is particularly highlighted due to the importance of preventing victimization in the digital space, which is closely related to the issue of adequate criminal law response. The authors point out the importance of continuous monitoring of research results on the state of digital crime, especially in the context of recognizing and incriminating new forms of criminal behaviour. In the digital era, the social response to crime is also transforming, in both of its forms: informal and formal. Analyzing individual aspects of both forms of social response, the authors point out both the positive and negative sides of this transformation.